2015
DOI: 10.1002/2015wr017032
|View full text |Cite
|
Sign up to set email alerts
|

Catchment coevolution: A useful framework for improving predictions of hydrological change?

Abstract: The notion that landscape features have coevolved over time is well known in the Earth sciences. Hydrologists have recently called for a more rigorous connection between emerging spatial patterns of landscape features and the hydrological response of catchments, and have termed this concept catchment coevolution. In this paper we review recent literature on this subject and attempt to synthesize what we have learned into a general framework that would improve predictions of hydrologic change. We first present … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

8
105
0

Year Published

2015
2015
2016
2016

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 120 publications
(122 citation statements)
references
References 119 publications
(184 reference statements)
8
105
0
Order By: Relevance
“…Present-day land surface characteristics in pristine landscapes have co-evolved over time through various interactions between the prevailing climates and geological settings (bedrock type, tectonic uplift) Troch et al, 2015). Hydrologists have coined the term catchment coevolution as a theoretical framework that seeks to formulate explanatory hypotheses about spatial patterns of landscape characteristics and the corresponding hydrological response, based on the historical development of catchments (Sivapalan et al, 2012;Troch et al, 2013;Harman and Troch, 2014).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Present-day land surface characteristics in pristine landscapes have co-evolved over time through various interactions between the prevailing climates and geological settings (bedrock type, tectonic uplift) Troch et al, 2015). Hydrologists have coined the term catchment coevolution as a theoretical framework that seeks to formulate explanatory hypotheses about spatial patterns of landscape characteristics and the corresponding hydrological response, based on the historical development of catchments (Sivapalan et al, 2012;Troch et al, 2013;Harman and Troch, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…One is direct control on the water balance by function of available water and energy (e.g., Budyko, 1974;Milly, 1994;Troch et al, 2009;Sivapalan et al, 2011). The other is indirect control on the hydrologic regime as one of four independent factors (climate, bedrock weatherability, tectonic uplift and time) that control the evolution of landscape properties (landforms, soils, and vegetation; Troch et al, 2015). For example, Gentine et al (2012) found that catchment-scale rooting depth was strongly correlated with the seasonal distribution of water and energy availability in 431 catchments in the United States.…”
Section: Introductionmentioning
confidence: 99%
“…As stated by Troch et al (2015), catchment co-evolution studies the process of spatial and temporal interactions between water, energy, landscape properties such as bedrock, soils, channel networks, sediments and anthropogenic influences that lead to changes of catchment characteristics and responses. In particular, landscape organization determines how a catchment filters climate into hydrological response in time.…”
Section: Searching For Signs Of Catchment Co-evolution: Power Law Parmentioning
confidence: 99%
“…In particular, landscape organization determines how a catchment filters climate into hydrological response in time. For this reason catchment co-evolution is not studied in the time domain, but from a spatial perspective (Perdigão and Blöschl, 2014;Troch et al, 2015).…”
Section: Searching For Signs Of Catchment Co-evolution: Power Law Parmentioning
confidence: 99%
“…The results of coevolution that can be captured in the 35 spatial patterns of landscape features including vegetation, geometry of stream networks, soil profiles control the hydrological response of the catchments. Recognizing this interconections, hydrologists have recently proposed the idea of catchment coevolution (Sivapalan et al, 2012;Troch et al, 2013;Harman and Troch, 2014;Troch et al, 2015). In the framework of the catchment coevolution, one seeks to find an empirical relationship between landscape features and the hydrological response, 40 and to decipher the causality of the relationship from the historical development of catchments.…”
mentioning
confidence: 99%